The Effect of Assertive Training on Bullying in Junior High School - Herman, Hermalinda; Nurshal, Deswita; Novrianda, Dwi (Jurnal Keperawatan Soedirman, 2020)
Bullying is a universal phenomenon and a common problem amongst school-aged children. Bullying can have a negative impact on the mental health and welfare of children. One strategy that can be done to prevent bullying is to practice assertiveness skills. This study aimed to identify the effect of assertiveness training in reducing bullying behaviour amongst students of Junior High School Padang. The study design was Quasi-experimental with a sample of 81 students (43 controls and 38 interventions). The intervention group received assertiveness training that consisted of 5 sessions, including communicating with others, declaring "no" to irrational requests, expressing complaints, rewarding others and accepting rewards and reinforcing the assertive behaviour with social-drama. Each session duration was 30-45 minutes. Adolescent Peer Relation Instrument (APRI) was applied to measure bullying behaviour. The statistical tests used were Wilcoxon and Mann Whitney. The results showed that there were differences in bullying behaviour before and after intervention between the control group and the intervention group (p-value 0.001). It can be concluded that assertiveness skills training could be maintained as an intervention that would be able to prevent bullying in adolescents.